Динаміка вмісту продуктів перекисного окислення ліпідів та антиоксидантів в крові щурів з кріодеструкцією шкіри та уведенням екстракту кріоконсервованих фрагментів шкіри поросят або водного колоїдного розчину фулерену С60 - Власов, О.О.; Ковальов, Г.О.; Чиж, М.О.; Гальченко, С.Є. (Вісник проблем біології і медицини. 2020 1 (155): 102–106., 2020)
Кріодеструкція шкіри супроводжувалася статистично значущим збільшенням в сироватці крові вмісту дієнових кон’югатів і ТБКАП. При цьому мало місце зменшення активності супероксиддисмутази і каталази. Застосування екстракту кріоконсервованих фрагментів шкіри поросят або водного колоїдного розчину фулерену С60 сприяло відновленню балансу про- і антиоксидантної систем у тварин з холодовими ранами, що проявляється нормалізацією вмісту ТБКАП і дієнових кон’югатів, а також підвищенням активності супероксиддисмутази і каталази до рівня норми в сироватці крові на 21 добу //////////////////////////////////////////////////////////////////////////////////////////////////////////////////////////// Cryodestruction is often used to treat skin tumors, since this method is the least traumatic, has no contraindications for the treatment of malignant neoplasm of external localizations. To restore the skin after cold injuries, various therapeutic methods are used to stimulate regeneration.Research aim was to evaluate the effects of cryopreserved extract of piglet’s skin fragments (PSE) or aqueous colloidal solution of fullerene C60 (FAS C60) on the intensity of lipid peroxidation (LPO) and the antioxidant enzymes activity in serum after local skin cryodestruction in rat.Research object and methods. The study was performed in 6-month-old hairless male rats in compliance with the requirements of the Bioethics Committee of the Institute for Problems of Cryobiology and Cryomedicine of the NAS of Ukraine. The low-temperature exposure on skin was done by cryoprobe (10 mm diameter, time was 120 s). FAS C60 was injected into the abdominal cavity daily in a single dose of 0.1 mg/kg body weight, starting from the day of cryodamage for 5 days. PSE were injected into the abdominal cavity daily during the entire experiment, the peptide dose was 50 μg per 100 g of weight. To assess the intensity of lipid peroxidation, the level of diene conjugates (DC) and thiobarbituric acid reactive substances (TBARS) was determined. Antioxidant activity was evaluated by the activity of superoxide dismutase (SOD) and serum catalase (CAT). Statistical processing of the results was carried out using the Kruskal-Wallis test using the software package STATISTICA 10.0 (StatSoft, USA). Results. On the 7th day of the experiment, the concentration of DC in serum was significantly higher than normal in all cases. On day 21, this indicator returns to normal values in groups of animals that were injected PSE or FAS C60. A similar situation was observed when studying the concentration of TBA-RS in rat serum. In all cases, a decrease of this indicator is observed on day 21. But only in groups that were treated with PSE or FAS C60, on the 21st day, the concentration of TBA-RS in blood serum was normalized. The activity of SOD on day 7 in all experimental groups was less than normal. On day 14, its activity was also less than normal, but in the group with PSE or FAS C60, it was higher than in the control group. On day 21 the activity of SOD in the experimental groups was normal. And it was significantly higher than in the control group. The dynamics of activity of CAT in serum was the same as the activity of SOD. Thus, the treatment with PSE or FAS C60 helped restore the balance of pro- and antioxidant systems in animals with skin cryodestruction, it manifests itself as a normalization of the content of TBARS and DC, as well as an increase in the activity of superoxide dismutase and catalase to normal levels in serum by 21 days.
ДИНАМИКА СОДЕРЖАНИЯ ПРОДУКТОВ ПЕРЕКИСНОГО ОКИСЛЕНИЯ ЛИПИДОВ И АНТИОКСИДАН- ТОВ В КРОВИ КРЫС С КРИОДЕСТРУКЦИЕЙ КОЖИ И ВВЕДЕНИЕМ ЭКСТРАКТА КРИОКОНСЕРВИРОВАННЫХ ФРАГМЕНТОВ КОЖИ ПОРОСЯТ ИЛИ ВОДНОГО КОЛЛОИДНОГО РАСТВОРА ФУЛЛЕРЕНА С60
THE DYNAMICS OF THE LIPID PEROXIDATION PRODUCTS AND ANTIOXIDANTS IN THE BLOOD AFTER SKIN CRYODESTRUCTION AND TREATMENT WITH CRYOPRESERVED EXTRACT OF PIGLET’S SKIN FRAG- MENTS OR AQUEOUS COLLOIDAL SOLUTION OF FULLERENE C60 IN RATS
Власов О.О., Ковальов Г.О., Чиж М.О., Гальченко С.Є. Динаміка вмісту продуктів перекисного окислення ліпідів та антиоксидантів в крові щурів з кріодеструкцією шкіри та уведенням екстракту кріоконсервованих фрагментів шкіри поросят або водного колоїдного розчину фулерену С60 . Вісник проблем біології і медицини. 2020 1 (155): 102–106.
Keywords: кріодеструкція шкіри; екстракт кріоконсервованих фрагментів шкіри поросят; розчин фулерену С60; ерекисне окислення ліпідів; активність антиоксидантних ферментів; skin cryodestruction; extracts of cryopreserved piglet skin fragments; solution of fullerene C60; lipid peroxidation; antioxidant enzymes activity